Causes and consequences of female centrality in cetacean societies. (15th July 2019) - Rendell, Luke; Cantor, Mauricio; Gero, Shane; Whitehead, Hal; Mann, Janet
Abstract : Cetaceans are fully aquatic predatory mammals that have successfully colonized virtually all marine habitats. Their adaptation to these habitats, so radically different from those of their terrestrial ancestors, can give us comparative insights into the evolution of female roles and kinship in mammalian societies. We provide a review of the diversity of such roles across the Cetacea, which are unified by some key and apparently invariable life-history features. Mothers are uniparous, while paternal care is completely absent as far as we currently know. Maternal input is extensive, lasting months to many years. Hence, female reproductive rates are low, every cetacean calf is a significant investment, and offspring care is central to female fitness. Here strategies diverge, especially between toothed and baleen whales, in terms of mother–calf association and related social structures, which range from ephemeral grouping patterns to stable, multi-level, societies in which social groups are strongly organized around female kinship. Some species exhibit social and/or spatial philopatry in both sexes, a rare phenomenon in vertebrates. Communal care can be vital, especially among deep-diving species, and can be supported by female kinship. Female-based sociality, in its diverse forms, is therefore a prevailing feature of cetacean societies. Beyond the key role in offspring survival, it provides the substrate for significant vertical and horizontal cultural transmission, as well as the only definitive non-human examples of menopause. This article is part of the theme issue 'The evolution of female-biased kinship in humans and other mammals'.